Clinical and molecular delineation of classical-like Ehlers–Danlos syndrome through a comprehensive next-generation sequencing-based screening system - Yamaguchi, Tomomi; Yamada, Kazuo; Nagai, So; Nishikubo, Toshiya; Koitabashi, Norimichi; Minami-Hori, Masako; Matsushima, Masaaki; Shibata, Yuka; Ishiguro, Hiroki; Sanai, Hiromi; Fujikawa, Tomomi; Takiguchi, Yuri; et al. (Frontiers in Genetics, 2023)
Classical-like Ehlers-Danlos syndrome (clEDS) is an autosomal recessive disorder caused by complete absence of tenascin-X resulting from biallelic variation in TNXB. Thus far, 50 patients from 43 families with biallelic TNXB variants have been identified. Accurate detection of TNXB variants is challenging because of the presence of the pseudogene TNXA, which can undergo non-allelic homologous recombination. Therefore, we designed a genetic screening system that is performed using similar operations to other next-generation sequencing (NGS) panel analyses and can be applied to accurately detect TNXB variants and the recombination of TNXA-derived sequences into TNXB. Using this system, we identified biallelic TNXB variants in nine unrelated clEDS patients.TNXA-derived variations were found in > 75% of the current cohort, comparable to previous reports.The current cohort generally exhibited similar clinical features to patients in previous reports, but had a higher frequency of gastrointestinal complications (e.g., perforation, diverticulitis, gastrointestinal bleeding, intestinal obstruction, rectal/anal prolapse, and gallstones). This report is the first to apply an NGS-based screening for TNXB variants and represents the third largest cohort of clEDS, highlighting the importance of increasing awareness of the risk of gastrointestinal complications.